2019
DOI: 10.1159/000496835
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to Cat: When Is Nasal Challenge Needed?

Abstract: Introduction: Although the skin prick test (SPT) is a reliable diagnostic tool in perennial allergic rhinitis (PER) for patients allergic to cats, the minimum necessary SPT wheal size required to distinguish cat sensitization from true allergy remains controversial. The cat nasal challenge test (cNCT) could be considered the gold standard for detecting true cat allergy. Aims: To assess the difference in the frequency of cNCT positivity between cat owners and non-owners and to determine an appropriate cut-off l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…In a different study in which 3068 patients, 16% of whom were pediatric patients, were evaluated, a 7 mm wheal size was determined for the development of allergic symptoms in cats with 80% PPV [ 21 ]. In a study evaluating 60 adult patients with AR, it was reported that a cut-off value of >6.5mm for cat allergy could avoid nasal provocation tests, which are often demanding and time-consuming [ 22 ]. While food provocation tests are the gold standard diagnostic method for food allergies, provocation tests for inhaled allergens are of limited practical use.…”
Section: Discussionmentioning
confidence: 99%
“…In a different study in which 3068 patients, 16% of whom were pediatric patients, were evaluated, a 7 mm wheal size was determined for the development of allergic symptoms in cats with 80% PPV [ 21 ]. In a study evaluating 60 adult patients with AR, it was reported that a cut-off value of >6.5mm for cat allergy could avoid nasal provocation tests, which are often demanding and time-consuming [ 22 ]. While food provocation tests are the gold standard diagnostic method for food allergies, provocation tests for inhaled allergens are of limited practical use.…”
Section: Discussionmentioning
confidence: 99%
“…Allergen avoidance or exposure reduction, where possible, is regarded as fundamental to managing allergies, 7,23,88,95,97…”
Section: Methods For Managing Cat Allergymentioning
confidence: 99%
“…Sensitisation (production of allergen-specific IgE9) is necessary for signs of respiratory allergy to develop, but not all sensitised individuals develop allergy symptoms since this depends on many factors, including the level of sensitisation (amount of allergen-specific IgE produced), the ‘allergenicity’ and amount of exposure to the antigen, and other environmental factors. 1 , 7 , 9 , 12 14 Cat allergy is reported to be approximately twice as common as dog allergy, 10 and many studies have reported a higher prevalence of sensitisation and/or allergy to cats. 4 , 15 21 Even in studies showing similar rates of sensitisation to dogs and cats, 7 , 11 cats may still be a more important cause of allergic symptoms due to quantitative and qualitative differences in the level of sensitisation, the allergenicity of cat antigens, and in exposure to allergens (which may be influenced by pet populations and differences in the physicochemical properties of the allergens).…”
Section: Prevalence Of Human Allergy To Catsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a safe and reasonably priced technique that replicates an allergic reaction in the nose under standardised and controlled conditions [19]. NPT aims to demonstrate the causal role of an allergen [23], to diagnose local allergic rhinitis [24], and to identify the clinically relevant allergen(s) in polysensitised subjects [25]. Therefore, it could lead to the application of stratified and personalised medicine in rhinitis patients [26].…”
Section: Introductionmentioning
confidence: 99%